2019
DOI: 10.1108/jcm-07-2018-2763
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of monetary discounts: comparing quantity scarcity and time restriction

Abstract: Purpose This study aims to examine whether adding a quantity scarcity message to a monetary discount helps to improve consumers’ offer-related perceptions and intentions, and how the effectiveness of that message compares with adding time restriction to the offer. Design/methodology/approach Two experiments, where participants evaluated retail ads and responded to relevant measures, were conducted in two country markets. Findings Adding either a quantity scarcity message or time restriction to a monetary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Second, it provides a conceptual framework for conducting a thorough assessment of the input communication and output persuasion factors in persuading consumers. Third, despite its limited application in tourism and hospitality, the matrix has been widely used in advertising and communication research (Jha, Dutta, and Koksal 2019; Zhou et al 2021), as it allows for in-depth examination of the communication–persuasion process and is especially useful in determining the effectiveness of the message, source, content, design, and diffusion channel (Muturi 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Second, it provides a conceptual framework for conducting a thorough assessment of the input communication and output persuasion factors in persuading consumers. Third, despite its limited application in tourism and hospitality, the matrix has been widely used in advertising and communication research (Jha, Dutta, and Koksal 2019; Zhou et al 2021), as it allows for in-depth examination of the communication–persuasion process and is especially useful in determining the effectiveness of the message, source, content, design, and diffusion channel (Muturi 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Non-conspicuous goods had greater attitudes (Gierl and Huettl, 2010) and utilitarian products (Ku et al, 2011) had greater purchase intentions for the high-demand group as compared to the limited-supply group. Non-conspicuous goods had greater purchase intentions for the limited-time group as compared to the limited-supply group (Jha et al, 2019). Both time restriction and countdown timer had greater attitudes and greater purchase intentions than no time restriction (Kim et al, 2020).…”
Section: Limited-time Message and Countdown Timermentioning
confidence: 86%
“…In a study of tablet computer advertisements and purchase intention, a limited-time message had a greater mean value than a limited-quantity message and the control group of no specific time or scarcity message had the lowest mean for purchase intention (Jha et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggarwal and Vaidyanathan, 2003;Devlin et al, 2007), comparing shoppers' responses to quantity scarcity and time restriction (e.g. Aggarwal et al, 2011;Jang et al, 2015;Jha et al, 2019;Mitomi, 2018). Though research has shown that individuals do use limited availability as a cue in evaluating offers (Gierl and Huettl, 2010;Inman et al, 1997), the particular strategy of restricting offers to specified outlets has not yet attracted significant interest in the literature.…”
Section: Introductionmentioning
confidence: 99%